Activation of the nucleotide excision repair pathway by crude oil exposure: A translational study from model organisms to the Hebei Spirit Oil Spill Cohort. (November 2019) - Kim, Youngho; Jeong, Jaeseong; Chatterjee, Nivedita; Yim, Un Hyuk; Kwon, Jung-Hwan; Park, Myung-Sook; Choi, Jinhee
Abstract: In order to gain insight into the human health implications of the Hebei Spirit Oil Spill (HSOS), the mechanism of toxicity of the Iranian heavy crude (IHC), the main oil component in the HSOS was investigated in Caenorhabditis elegans and zebrafish . The identified mechanism was translated to humans using blood samples from Taean residents, who experienced HSOS with different levels of exposure to the spill. C. elegans TF RNAi screening with IHC oil revealed the nucleotide excision repair (NER) pathway as being significantly involved by oil exposure. To identify the main toxicity contributors within the chemical mixture of the crude oil, further studies were conducted on C. elegans by exposure to C3-naphthalene, an alkylated polycyclic aromatic hydrocarbon (PAH), which constitutes one of the major components of IHC oil. Increased expression of NER pathway genes was observed following exposure to the IHC oil, C3-naphthalene enriched fraction and C3-naphthalene. As the NER pathway is conserved in fish and humans, the same experiment was conducted in zebrafish, and the data were similar to what was seen in C. elegans . Increased expression of NER pathway genes was observed in human samples from the high exposure group, which suggests the involvement of the NER pathway in IHC oil exposure. Overall, the study suggests that IHC oil may cause bulk damage to DNA and activation of the NER system and Alkylated PAHs are the major contributor to DNA damage. Our study provides an innovative approach for studying translational toxicity testing from model organisms to human health. Graphical abstract: Image 1 Highlights: Human health implications of HSOS was investigated in C.elegans, zebrafish and human blood samples from HSOS cohort. C. elegans transcription factors RNAi library screening revealed NER pathway as a mechanism of toxicity of crude oil. Alkylated PAHs seemed to be the major contributors of crude oil exposure-induced DNA damage and repair. Alteration of NER pathway by crude oil exposure was a conserved response in C.elegans, zebrafish and human cohort samples. Toxicological and epidemiological approaches can be complementarily used for identifying mechanism of toxicity of chemicals and their consequences to human health. Abstract : Main finding: Model organisms-based toxicological and cohort-based epidemiological studies collectively suggest that involvement of the NER pathway in the toxicity of IHC oil from the 2007 HSOS.